1994
DOI: 10.1063/1.357780
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crystal growth on Ti3+ centers in KTiOPO4

Abstract: A series of Ti3+ centers have been formed in hydrothermally grown and flux-grown potassium titanyl phosphate (KTiOPO4 or KTP). These 3d1 defects (S=1/2) were created with 60 kV x rays at 77 K, and electron paramagnetic resonance and electron-nuclear double-resonance (ENDOR) data were taken below 30 K. The ENDOR spectra show that the two Ti3+ centers having the largest concentrations in hydrothermally grown KTP have a neighboring proton, presumably in the form of an adjacent OH− ion. In contrast, ENDOR spectra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…In fact, SH generation along the axis of PC crystals is a parasitic, undesirable effect due to its possible negative consequences: nonlinear absorption increasing within the visible and near-IR wavelength ranges and the grey track formation. This effect was observed in multiple experimental studies [57][58][59][60]. Grey track formation was also reported in KTP crystals under UV radiation [57,61,62], which is similar to the effects induced by SH of the Nd:YAG laser radiation.…”
Section: Introductionsupporting
confidence: 72%
“…In fact, SH generation along the axis of PC crystals is a parasitic, undesirable effect due to its possible negative consequences: nonlinear absorption increasing within the visible and near-IR wavelength ranges and the grey track formation. This effect was observed in multiple experimental studies [57][58][59][60]. Grey track formation was also reported in KTP crystals under UV radiation [57,61,62], which is similar to the effects induced by SH of the Nd:YAG laser radiation.…”
Section: Introductionsupporting
confidence: 72%
“…Thus, a few of the electrons and holes will be stabilized at widely separated sites within the crystal and form the point defects (optical absorption centres) that contribute to the formation of a gray track [6]. Primal scholars [1,4,7] suggested that Ti 3+ may cause optical damage but this didn't give any direct relation to the cause of gray tracking, there after Scripsick MP et al [8] have overcome above statement, by experimentally proving that Fe 3+ traps holes and Ti 3+ traps electron, Nizamutdinov et al [9]. Experiments proved existence of EPR spectra Fe 3+ in KTP for the first time following him Stenger et al [10] and Gaite [11] distinguished four spectra of Fe 3+ in flux grown KTP, latter studies suggested that Fe 3+ occupy Ti(1) and Ti(2) sites depend on crystal and ENDOR(electron-nuclear double resonance) studies by Scrip sick suggested that oxygen vacancies are located adjacent to the Ti 3+ centres also (Figures 1 & 2) [8] depict EPR results conformance with all these theory basis they forwarded to trapping sites identification in flux grown crystal and induced gray track through x-ray source where the effect was found at 500nm due to Fe 3+ other negligible effect due to Fe 2+ or Fe 4+ also seen in (Figure 1) [8].…”
Section: Mechanism Involved In Gray Tracking Formationmentioning
confidence: 99%
“…The crystal structure of KTP (space group Pna21) consists of threedimensional network of TiO6 octahedral and PO 4 tetrahedral [32]. There are structural channels parallel to the polar c axis through which the K + ions can easily move under the influence of an electric field by a vacancy mechanism, (similar to one of two sub system modelled by Murk V [7] leading to a high ionic conductivity along this direction emphasized by Morris PA [33]. Gray tracks produced in KTiOPO 4 (KTP) by applying a dc electric field have been studied through optical absorption, Raman scattering, and synchrotron x-ray topography.…”
Section: Electrically Induced Gray Trackmentioning
confidence: 99%
“…of these Ti 3+ centers is located adjacent to an oxygen vacancy. 38 We found that Center A (in Roelofs' notation) is the dominant center after an irradiation at room temperature; it has a concentration at least twenty times greater than any of the other three Ti 3+ centers.…”
mentioning
confidence: 94%
“…We attribute these additional splittings to neighboring phosphorus nuclei, in analogy with the phosphorus hyperfine always exhibited by the various Ti 3+ centers in KTP. 38 ' 39 In contrast, Pt(B)…”
Section: A Platinum-associated Electron and Hole Trapsmentioning
confidence: 99%